(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The objective of this research was to develop and optimize topical gel containing Aceclofenac using quality by design QbD based on a 23 factorial design. Aceclofenac is a non-steroidal anti-inflammatory drug used for the treatment of pain and inflammation. Aceclofenac is insoluble in water and may cause gastrointestinal side effects being a BCS class II drug. In order to decrease gastric ulcerogenic effects, gels have been developed. The optimized gel showed improved saturation solubility of (0.091+0.009) to the corresponding physical mixture of pure Aceclofenac